Pengembangan Human Capital Dalam Mendukung Perilaku Kerja dan Kinerja Dosen Akademi Sekretari dan Manajemen Ariyanti - Permana, Tatiek Ekawati; Yuniarsih, Tjutju; Ahman, Eeng; Wibowo, Lili Adi; Wiyono, Darul (Jurnal Manajemen, 2022)
Research problems are related to the quality of human resources from the aspects of intellectual capital and the performance of the tridharma of lecturers in the fields of education and teaching, research and scientific publications and community service. Interventions needed to resolve Human Resources and performance problems can be carried out through a process of training and intellectual capital development. This study aims to examine and evaluate the contribution of formal education and non-formal education variables in supporting the development of intellectual capital, work behavior and performance of Ariyanti Academy of Secretarial and Management lecturers. This type of research is a quantitative study using a survey method at the Academy of Secretary and Management Ariyanti through giving questionnaires to 59 lecturers. The results of the research found that: (1) formal education and non-formal education contributed positively and significantly in supporting intellectual capital, (2) work behavior contributed positively and significantly in supporting the performance of the tridharma of lecturers, and (3). intellectual capital contributes positively and significantly in supporting the tridharma performance of Ariyanti Academy of Secretarial and Management lecturers.